1997
DOI: 10.1021/jp970283q
|View full text |Cite
|
Sign up to set email alerts
|

On the Diffusion Impedance at Semiconductor Electrodes

Abstract: It is well known that at metal electrodes, mass transport limitations introduce a Warburg impedance in the electrochemical impedance of an electrode process. Semiconductor electrodes, however, react differently from metal electrodes to variations of the applied potential, so that the influence of diffusion on the electrochemical impedance is less straightforward. In this paper, we propose a general approach of this problem, allowing to describe both the metal and semiconductor electrode behavior by using appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Similar shapes of the impedance diagrams were obtained by other researchers who performed EIS measurements with semiconductor electrodes such as iron oxides (Fe 1 [14]), boron-doped diamond films on molybdenum substrates [20], and Si, Sn and Zn-doped n-GaAs, n-InP and p-InP electrodes [18]. Aroutiounian [13,14] also suggested that the main contribution to the impedance at high frequencies (> 10 kHz) is the space charge layer of the semiconductor, while at low frequencies (< 10 kHz) a slow diffusion process dominates the impedance spectra.…”
Section: Equivalent Circuit Modelssupporting
confidence: 83%
See 1 more Smart Citation
“…Similar shapes of the impedance diagrams were obtained by other researchers who performed EIS measurements with semiconductor electrodes such as iron oxides (Fe 1 [14]), boron-doped diamond films on molybdenum substrates [20], and Si, Sn and Zn-doped n-GaAs, n-InP and p-InP electrodes [18]. Aroutiounian [13,14] also suggested that the main contribution to the impedance at high frequencies (> 10 kHz) is the space charge layer of the semiconductor, while at low frequencies (< 10 kHz) a slow diffusion process dominates the impedance spectra.…”
Section: Equivalent Circuit Modelssupporting
confidence: 83%
“…As the surface of the In 0.2 Ga 0.8 N electrode is covered by a layer of specifically and nonspecifically adsorbed anions, the electroactive ion species in the solution must diffuse through this layer in order to reach the surface of the electrode and participate in a charge transfer reaction (oxidation or reduction through exchange of electrons via the conduction band of the semiconductor). As the small potential perturbation applied during the EIS experiments affects the rate of this diffusion process, it in turn influences the electrochemical impedance of the system [18].…”
Section: Resultsmentioning
confidence: 99%
“…The theoretically predicted AC impedance response was compared with experiments on n-GaAs rotating disk electrodes in sulfuric acid media [79]. The equivalent circuit in Fig.…”
Section: Dark Processes Mediated By Surface States or By Space Charge...mentioning
confidence: 99%
“…As in the latter case, hydrodynamic voltammetry is best suited to study mass transport. AC impedance spectroscopy can be another useful tool in this regard [105].…”
Section: Rate-limiting Steps In Charge Transfer Processes In the Darkmentioning
confidence: 99%
“…Their influence on the electrochemical responses and its application lies at the heart of modern day electrochemical devices like batteries [6,7], fuel cells [8,9], electrochromic smart windows [10], ion exchange membranes [11], solar cells [12], capacitive deionization cells [13], supercapacitors [13], nanostructured semiconductor electrodes [14], electrochromic films [10,15], and ion intercalation in nanostructured materials [7,16]. It is well known that the geometrical and morphological characteristics like non-uniformities of the surface, viz.…”
Section: Introductionmentioning
confidence: 99%